2011
DOI: 10.1021/nn103317u
|View full text |Cite
|
Sign up to set email alerts
|

Helical Encapsulation of Graphene Nanoribbon into Carbon Nanotube

Abstract: Molecular dynamics (MD) simulations were performed to study interaction between the graphene nanoribbon (GNR) and single-wall carbon nanotube (SWCNT). The GNR enters the SWCNT spontaneously to display a helical configuration which is quite similar to the chloroplast in the spirogyra cell. This unique phenomenon results from the combined action of the van der Waals potential well and the π-π stacking interaction. The size of SWCNT and GNR should satisfy some certain conditions in the helical encapsulation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 49 publications
2
53
0
1
Order By: Relevance
“…Moreover, according to the proposed geometrical structures of GNRs in CNTs by Jiang et al 7,. we speculate that the flexible ribbons twist to adopt a versatile orientation222324 under such moderate heating condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, according to the proposed geometrical structures of GNRs in CNTs by Jiang et al 7,. we speculate that the flexible ribbons twist to adopt a versatile orientation222324 under such moderate heating condition.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies devoted to the fabrication of graphene nanoribbons (GNRs) in CNTs through the confined polymerization of polycyclic aromatic hydrocarbon molecules56. In addition, the theoretical models proposed by Jiang et al 7. have suggested that the GNRs residing in CNTs would form a helical conformation due to the geometric constraints imposed by an outer tube.…”
mentioning
confidence: 99%
“…250 It was recently demonstrated that it may be possible to combine graphene and carbon nanotubes in novel composite materials in which the graphene spontaneously rolls up around the nanotube or enters its interior. [251][252][253][254] Graphene can also interact with carbon nanotubes to form 3D pillared structures where individual graphene sheets are separated by perpendicularly oriented carbon nanotubes. MD techniques were used to study the mechanical and thermal properties of these nano-networks, 255,256 and there is computational evidence that such pillared graphene structures could be used in gas separation 257 or hydrogen storage.…”
Section: Hybrid Carbon Systemsmentioning
confidence: 99%
“…22 Moreover, the COMPASS potential has been widely used to model the carbon-carbon bond of graphene. [32][33][34][35][36][37] The second reason is that the grillage model is anisotropic and the materials properties are highly dependent on the deformation modes. Wrinkles in graphene herein are generally nonsymmetrical deformation.…”
Section: Comparison Of Recommended Grillage Parameters With Reportmentioning
confidence: 99%